2021
DOI: 10.2174/1386207323666200914100119
|View full text |Cite
|
Sign up to set email alerts
|

Detection of MCR-1 Gene in Multiple Drug Resistant Escherichia coli and Klebsiella pneumoniae in Human Clinical Samples from Peshawar, Pakistan

Abstract: Background: The presence of plasmid mediated mcr-1 gene in multidrug resistant Gram-negative bacteria poses a serious public health concern in today’s world. Objectives: The present study was aimed to detect the presence of plasmid mediated mcr-1 encoding resistance to colistin in multiple drug resistant (MDR) E. coli and K. pneumoniae isolates. Methods: A total 180 clinical isolates of E. coli (n=120) and K. pneumoniae (n=60) were isolated from different clinical specimens i.e. urine, blood, stool and pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 28 publications
1
7
0
Order By: Relevance
“…15 Another study done in Peshawar indicated that 40% Klebsiella pneumoniae and 23% E.coli showed resistance to colistin. 4 Colistin resistant E.coli showed resistance to ciprofloxacin 81.2%, Amoxicillin and clavulanic acid 70.8%, Ceftazidim 66.7%, Cefepime 50% and Cefotaxim 77.1% in this study. These results are comparable to other study done in china.…”
Section: A H E a D O F P R I N Tsupporting
confidence: 49%
See 2 more Smart Citations
“…15 Another study done in Peshawar indicated that 40% Klebsiella pneumoniae and 23% E.coli showed resistance to colistin. 4 Colistin resistant E.coli showed resistance to ciprofloxacin 81.2%, Amoxicillin and clavulanic acid 70.8%, Ceftazidim 66.7%, Cefepime 50% and Cefotaxim 77.1% in this study. These results are comparable to other study done in china.…”
Section: A H E a D O F P R I N Tsupporting
confidence: 49%
“…E-mail: drihsan.ibms@kmu.edu.pk medical community to reconsider the colistin for the treatment of Multidrug resistant gram negative bacteria worldwide. 4,5 Colistin is an old antibiotic, which also known as polymyxin E antibiotic which was approved by the FDA in 1959. 6 It is widely used for the treatment of animals and now increasingly given worldwide to human for the treatment of multi drug resistant bacteria e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Peshawar, Pakistan, a study reported 5% mcr-1 out of 120 multiple drug-resistant E. coli . 42 Similarly, a study from Faisalabad, Pakistan, detected one mcr-1 bearing E. coli out of 29 ESBL producing strains. 15 The two earlier reported studies and our current study are from different geographical regions in Pakistan.…”
Section: Discussionmentioning
confidence: 95%
“…In Pakistan mcr-1 gene has been detected in 23.3% E. coli (n = 120) and 40% of K. pneumoniae (n = 60) [ 24 ]. Our study however revealed absence of mcr-1 gene in all isolates tested.…”
Section: Phylogenetic Analysismentioning
confidence: 99%